Coacervation between Two Positively Charged Poly(ionic liquid)s. Issue 18 (8th June 2022) - Zhang, Chongrui; Cai, Yinmin; Zhao, Qiang
Abstract: Complex coacervates are usually formed through electrostatic attraction between oppositely charged polyelectrolytes, with a few exceptions such as coacervates of like‐charge proteins and polyelectrolytes, both in vivo and in vitro. Understanding of the preparation and mechanisms of these coacervates is limited. Here, a positively charged poly(ionic liquid), poly(1‐vinyl‐3‐benzylimidazolium chloride) (PILben), is designed that bears benzene rings in repeating units. Fluidic coacervates are prepared by mixing the PILben aqueous solution with a like‐charge poly(ionic liquid) named poly(dimethyl diallyl ammonium chloride) (PDDA). The effects of polymer concentration, temperature, and ionic strength in the PILben‐PDDA coacervate are studied. Raman spectroscopy and 2D 1 H‐ 13 C heteronuclear single quantum coherence ( 1 H‐ 13 C HSQC) characterizations verify that the coacervate formation benefits from the cation‐ π interaction between PILben and PDDA. This work provides principles and understandings of designing coacervates derived from like‐charge poly(ionic liquids) with high charge density. Abstract : A poly(ionic liquid) bearing benzene rings is designed to facilitate facile preparation of coacervate between like charge polymers, providing a versatile platform of coacervate engineering. Phase behaviors of the coacervate are studied, with the cation‐ π driven force characterized in depth by 2D NMR and Raman spectroscopy.